Koconogi čuk Aegolius funereus najden na Ljubljanskem barju - Tome, Davorin (Acrocephalus, 2000)
On April 16th 1991 and March 13th 1997, feathers of Tengmalm's owls Aegolius furnereus were found at two plucking posts in the remains of a raised bog nearGoričica at Ljubljansko barje. The finds are the first records on the occurrence of this species outside its nest-site in nonbreeding season in Slovenia. The differences between primaries and tail feathers of the Tengmalm's owl and little owl Athene nocyua are described.
Keywords: bird; Birds; ptice; Ecosystem; ornitologija; čuki